2008
DOI: 10.1111/j.1474-919x.2008.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Moulting strategies of a long‐distance migratory seabird, the Mediterranean Cory's ShearwaterCalonectris diomedea diomedea

Abstract: Seabird moult is poorly understood because most species undergo moult at sea during the non‐breeding season. We scored moult of wings, tail and body feathers on 102 Mediterranean Cory's Shearwaters Calonectris diomedea diomedea accidentally caught by longliners throughout the year. Primary renewal was found to be simple and descendant from the most proximal (P1) to the most distal (P10) feather. Secondaries showed a more complex moulting pattern, with three different asynchronous foci: the first starting on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 52 publications
7
57
0
Order By: Relevance
“…Nevertheless, (primary) moultbreeding overlap does occur in petrels that are longdistance migrants (e.g. Alonso et al 2009), as birds have the option of starting moult while still breeding, and then suspending it until after they reach the winter quarters (Ramos et al 2009). This allows them to migrate without the need to allocate energy and nutrients to feather synthesis, as well as avoid costs related to gaps in the wing plumage at a time when efficiency during long-distance flight is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, (primary) moultbreeding overlap does occur in petrels that are longdistance migrants (e.g. Alonso et al 2009), as birds have the option of starting moult while still breeding, and then suspending it until after they reach the winter quarters (Ramos et al 2009). This allows them to migrate without the need to allocate energy and nutrients to feather synthesis, as well as avoid costs related to gaps in the wing plumage at a time when efficiency during long-distance flight is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…Seabird catches of LLPB are very erratic, showing high catch concentrated in a few sets. Other authors provide records regarding the unusually high catch of Procellariformes in undefined longlines in North East peninsular waters: 32 Calonectris diomedea on October 5 th 2004 (Ramos et al 2009) and at least 60 Puffinus mauretanicus on (Carboneras, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
“…Since the incubation routine in petrels depends on relief by the partner, males and females of both subspecies need to forage relatively close to the breeding colony ( Warham 1990). During the chick-rearing period, both satellite-tracking data and stable isotope values from the P1 (moulted during chick-rearing period, Ramos et al 2009) revealed a spatial segregation in foraging areas between subspecies. We found that all satellitetracked individuals of C. d. diomedea foraged exclusively in proximity to the breeding colony in the Mediterranean waters, whereas satellite-tracked Similarly to P1, we found a significant difference between subspecies in the isotopic values in S8 (moulted during migration, Ramos et al 2009), also suggesting spatial segregation between the subspecies in winter.…”
Section: Discussionmentioning
confidence: 99%